Stripping Voltammetry at Microdisk Electrode Arrays: Theory - Cutress, I; Compton, R (2009)
Anodic stripping voltammetry (ASV) is an extremely powerful tool for detection of metal ions in solution through a two step process of preconcentration of the metal at the electrode surface, followed by electrodissolution. The second phase produces an electroanalytical response proportional to the amount of material deposited in the first phase. This paper utilizes theory to explore the electrochemical signals produced when considering ASV at a microelectrode or ultramicroelectrode arrays. The theory outlined is applicable mostly to thin mercury film absorption and metal adsorption. © 2009 Wiley-VCH Verlag GmbH and Co. KGaA, Weinheim.